Application of a simple mono window land surface temperature algorithm from landsat ETM+ over al Qassim, Saudi Arabia - Lim, H.S; Mat Jafri, M·Z; Abdullah, K; Sultan AlSultan, (Universiti Kebangsaan Malaysia, 2012)
This study was conducted to retrieve the land surface temperature (LST) from Landsat ETM+ data for Al Qassim, Saudi Arabia. The proposed technique employed a mono window LST algorithm for retrieving surface temperature from Landsat ETM+. The land surface emissivity and solar angle values were needed in order to apply these in the proposed algorithm. The surface emissivity values were computed based on the NDVI values. The LST values derived from ATCOR2_T in the PCI Geomatica image processing software was used for algorithm calibration. The results showed a high correlation coefficient (R) and low root-mean-square error (RMS) between the LST values retrieved from the proposed algorithm and ATCOR2_T. This study indicated that the proposed algorithm is capable of retrieving accurate LST values and the derived information can be used in the environmental impact assessment for Al Qassim area.